Procedings of the British Machine Vision Conference 1990 1990
DOI: 10.5244/c.4.37
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of visual appearance

Abstract: This paper presents a method for reconstructing the visual appearance of a scene from any viewpoint, given a collection of stereo pairs. A representation is suggested which is flexible and efficient, and algorithms to recover three dimensional structure and grey-level detail by combining a number of two-dimensional views are discussed. Some results using real and simulated data are given. This paper presents a method for reconstructing the visual appearance of a scene from any viewpoint given a collection of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…• Grey-level modelling Methods for generating these models automatically from real images are being studied by North [7,8]. The use of non-uniform sampling (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Grey-level modelling Methods for generating these models automatically from real images are being studied by North [7,8]. The use of non-uniform sampling (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that such grey-level models can be computed automatically (e.g. [7,8]) and rendered in real time. The expense of this is partly offset by savings when inverting the perspective transform (since more consistent error vectors yield faster iterative solutions).…”
mentioning
confidence: 99%
“…This occurs when the measured surface occludes itself on projection, or when some surface already represented in the model is occluding. The self-occlusion problem can be solved by z-buffering during projection [5] but occlusion by other surfaces is more problematic.…”
Section: Surface Clusteringmentioning
confidence: 99%
“…The problem of estimating a single optimal surface from noisy measurements occurs in many vision and robotics applications [1,2,3,4]. Here it is considered in the context of building a description of a complex object or environment using stereo reconstruction from many viewpoints [5]. A definition is offered of the optimal surface to represent a set of measured surfaces, and the paper shows how it may be found using the Kalman filter framework.…”
mentioning
confidence: 99%